PENERJEMAHAN KATA-KATA BUDAYA BAHASA INDONESIA KE DALAM BAHASA INGGRIS - Nuryadi . (Fakultas Komunikasi, Sastra, dan Bahasa, 2016)
Translating of cultural words often face problems if it is not found the same cultural concept in target language so that it is not found the appropriate equivalence. The purpose of this research is to know the cultural categories in source language and the translating strategies used. This is the descriptive qualitative research about content analysis. Based on the analysis of data, it is found nineteen cultural words that is (1) material culture such as bicycle rickshaw, batik, trek, temple, coconut wine, and canting; (2) social culture such as elder, combatant, sultans; (3) art such as Ramayana, dalang, wayang kulit; and (4) ecology such as pandanas, and buffalo. There are two strategies used by translator, namely (1) there are twelve words which are translated using borrowing words; and (2) there are seven words which are translated using cultural equivalent or cultural substitution. The accuracy of cultural-word translation is very good, it is shown by successfulness to convey source language into target language meaning. Translator used more borrowing-word strategies than cultural equivalent because the nuance of source language culture is stronger.